Pertumbuhan Optimum Penicillium spp. dan Cunninghamella spp. yang Diisolasi dari Pakan dan Efek Toksiknya pada Mencit (Mus musculus) - N Ramli; M Tafsin; A D Hasjmy (Faculty of Animal Science, Bogor Agricultural University, 2009)
Fungi are a major microorganism present in the feedstuffs that able to reduce nutritive value and produce toxin that harmful for animal. Penicillium spp. and Cunninghamella spp. were dominant present in the feedstuffs in tropical regions. The objectives of this study were to find out the optimum pH and temperature of Penicillium spp. and Cunninghamella spp. on agar media and to find out the effect of feeding diet containing corn contaminated with the fungi at level of 0%, 50% and 100% on the performance and relative organ weight of 45 mice (Mus musculus). Cunninghamella spp. grew at pH range of 3-9, and Penicillium spp. at pH range of 3-7. The temperature for the optimum growth of both fungi was on room temperature (28±2 oC). Feed consumption and daily gain (ADG) of mice were not significantly affected by content of corn contaminated with Cunninghamella spp. Conversely, corn contaminated with Penicillium spp. significantly (P < 0.05) reduced feed consumption and ADG of mice. Treatments had no effect on liver and hearth relative weight, but significantly influenced relative weight of kidney and lymph. Lymph relative weight of mice fed ration containing Penicillium-contaminated corn was lower (P < 0.05) than that of control. Mice treated with contaminated corn from both fungi at the level 100% also significantly (P < 0.05) had higher kidney relative weight than that of control. It was concluded that the toxic effect of Penicillium spp. was higher than that of Cunninghamella spp. Key words: fungi, feedstuffs, growth, toxin, mice